Structural and Thermodynamics Properties of TiC1−xNx–TiO1−xNx Solid Solutions: X‐ray Diffraction and First‐Principles Approaches. Issue 4 (7th January 2014) - Jiang, Bo; Ying, Nantao; Wang, Qiuyu; Xiao, Jiusan; Huang, Kai; Hou, Jungang; Zhu, Hongmin; Besmann, T.
<x xml:space="preserve">Abstract</x> The structural properties and mixing thermodynamic of TiC1−xNx and TiO1−xNx (0 ≤ x ≤ 1) solid solutions have been studied by X‐ray diffraction method and first‐principles calculations. The TiC1−xNx and TiO1−xNx compounds were synthesized via solid‐state reaction and the analysis of XRD patterns show the properties of continuous solid solutions over the whole composition range. Thermodynamic analyses and structural stability studies were performed based on the mixing enthalpies and electronic structures. The mixing enthalpies of TiC1−xNx and TiO1−xNx can be fitted using a second‐degree polynomial with the increasing of supercell. The first‐principles calculations results reveal that the TiO1−xNx shows large number vacancies segregated in TiO‐part. The charge redistributed around Ti vacancy constitutes the main contribution to the stabilization rather than the Ti–Ti bond across the O vacancy through analyzing the electron density difference plots and PDOS . These results provide theoretical basis for the development and application of the TiC1−xNx and TiO1−xNx solid solutions.